Laser projector method for measuring postoperative acetabular anteversion after total hip replacement - Chen, Wei-Cheng; Wu, Tai-Yin; Chi, Kuan-Yu; Weng, Pei-Wei; Huang, Yu-Min; Lin, Yi-Chia; Liaw, Chen-Kun (Frontiers in Surgery, 2022)
Introduction For patients undergoing THR, measuring the postoperative acetabular anteversion precisely plays a pivotal role in the prognosis. However, using elliptical methods mandates computerized equipment that is frequently in shortage in remote areas and developing countries. We invented a laser projector utilizing the ellipse method to measure the acetabular anteversion directly. The aim is to examine the consistency and validity of the laser projector as compared to our original software, Elliversion. Materials and Methods We retrospectively collected 50 postoperative pelvis radiographs including acetabulum from our institution. One investigator first measured the anteversion of included radiographs through Elliversion software as the control group. Subsequently, two operators independently used the laser projector for measurements in two separate periods with 1-day intervals as the experimental group. Our analysis was comprised of intra- and inter-observer comparisons and reliability, which investigated both the consistency and validity, by using two-sample student’s t-test and intraclass correlation coefficient. Results There was no significant difference in measuring the anteversion through laser projectors between two operators (p=0.54), with excellent inter-observer reliability (ICC, 0.967). The estimated effect in the anteversion measurement between the Elliversion and laser projector was also comparable, with the ICC level of 0.984, indicating excellent reliability. Conclusion Our study reported the consistency and validity of this laser projector as there is no significant difference between Elliversion and Laser projector, notably with excellent intra- and inter-observer reliability. We look forward to helping elevate clinical acumen when doctors provide care to patients after THR, especially in remote areas.